Estimación porcentual de incidencia de problemas estructurales originados por errores en el diseño y construcción de instalaciones hidrosanitarias en Riobamba - Orozco Vallejo, Lizbeth Nataly (2021)
The city of Riobamba presents a great demand in construction of civil structures, causing the number of constructions to increase rapidly and sometimes in a disorderly manner, reason for which the compliance of certain regulations and design controls can be overlooked, causing failures in the structures. There are a lot of activities that must be considered when constructing a building, one of them being the plumbing installations, which are a fundamental part of the building's wellbeing. The present work focused precisely on these facilities considering that errors can occur in the design and construction of plumbing facilities causing structural problems, which were identified through a quantification in the northern sector of the city, specifically in neighborhoods adjacent to the National University of Chimborazo (UNACH), North Campus "Edison Riera", considered an area of growth and expansion. For this purpose, a field survey was carried out in which the structures were catalogued as affected, not affected or not identified, subsequently using the ArcGIS tool to mark the affected properties, and in this way obtain the percentage of affected, giving as a result that 35.22% of the buildings are affected by this problem, observing that the most recurrent failure is the cut in beams caused by the passage of the hydro-sanitary installations, thus reducing their working area.